2019
DOI: 10.1136/bmjgast-2019-000293
|View full text |Cite
|
Sign up to set email alerts
|

Impact of introducing a faecal immunochemical test (FIT) for haemoglobin into primary care on the outcome of patients with new bowel symptoms: a prospective cohort study

Abstract: ObjectiveTo determine whether a faecal immunochemical test (FIT) for faecal haemoglobin concentration (f-Hb) can be safely implemented in primary care as a rule-out test for significant bowel disease (SBD) (colorectal cancer (CRC), higher risk adenoma (HRA) and inflammatory bowel disease (IBD)) when used as an adjunct to the clinical assessment of new bowel symptoms.DesignSingle-centre prospective cohort study of all patients who attended primary care and submitted a FIT in the first calendar year of the servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
92
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(103 citation statements)
references
References 28 publications
(31 reference statements)
8
92
1
1
Order By: Relevance
“…Our findings broadly concur with previous research, and in particular outcomes in Scotland where FIT has been used in symptomatic patients for longer – although there are appreciable differences in the way challenges around pathway specifics, FIT analysers and inclusion/exclusion criteria used have been met . Nevertheless, we show that only 0.2% of patients with the lowest f‐Hb concentrations were found to have CRC when investigated, and reassuringly this is the same ‘miss rate’ reported for very low f‐Hb concentrations with longer follow‐up in Scotland . This ‘miss rate’ is an order of magnitude lower than NICE’s threshold of a 3% detection rate and should reassure other English centres, and indeed groups elsewhere, that are considering the incorporation of FIT into local 2WW pathways or equivalent.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings broadly concur with previous research, and in particular outcomes in Scotland where FIT has been used in symptomatic patients for longer – although there are appreciable differences in the way challenges around pathway specifics, FIT analysers and inclusion/exclusion criteria used have been met . Nevertheless, we show that only 0.2% of patients with the lowest f‐Hb concentrations were found to have CRC when investigated, and reassuringly this is the same ‘miss rate’ reported for very low f‐Hb concentrations with longer follow‐up in Scotland . This ‘miss rate’ is an order of magnitude lower than NICE’s threshold of a 3% detection rate and should reassure other English centres, and indeed groups elsewhere, that are considering the incorporation of FIT into local 2WW pathways or equivalent.…”
Section: Discussionsupporting
confidence: 90%
“…Our pathway and the ‘window’ process demonstrate one method of allaying concern around the introduction of FIT and minimizing any negative potential impact on NICE’s ‘high risk’ symptom groups . Our findings broadly concur with previous research, and in particular outcomes in Scotland where FIT has been used in symptomatic patients for longer – although there are appreciable differences in the way challenges around pathway specifics, FIT analysers and inclusion/exclusion criteria used have been met . Nevertheless, we show that only 0.2% of patients with the lowest f‐Hb concentrations were found to have CRC when investigated, and reassuringly this is the same ‘miss rate’ reported for very low f‐Hb concentrations with longer follow‐up in Scotland .…”
Section: Discussionsupporting
confidence: 86%
“…This finding adds weight to the approach of using FIT to risk‐stratify, and triage accordingly, patients of all ages who present to their primary healthcare providers with lower gastrointestinal symptoms. Some jurisdictions in the United Kingdom have adopted this approach in order to rationalize use of the stressed public colonoscopy resource . If FIT testing does not change the urgency category (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has since been published in support the use of low‐threshold FIT in symptomatic primary care patients 5,18‐25 . A Danish study concluded that FIT may be used as a supplementary diagnostic test in individuals with non‐alarm symptoms of colorectal cancer to diagnose serious bowel disease (colorectal cancer, high‐risk adenoma and inflammatory bowel disease) 24 .…”
Section: Introductionmentioning
confidence: 99%
“…A Danish study concluded that FIT may be used as a supplementary diagnostic test in individuals with non‐alarm symptoms of colorectal cancer to diagnose serious bowel disease (colorectal cancer, high‐risk adenoma and inflammatory bowel disease) 24 . Authors of a Scottish study strongly recommended FIT should become integral to the assessment of all patients presenting to primary care with new bowel symptoms, to objectively determine the risk of underlying serious bowel disease 20 . Despite these important studies, data from symptomatic primary care patients prior to referral are lacking 6 .…”
Section: Introductionmentioning
confidence: 99%